First results of long-term follow-up of children in Russia after gene therapy for hereditary retinal dystrophies associated with biallelic mutations in the RPE65 gene - V. V. Neroev; L. A. Katargina; M. P. Kharlampidi; L. V. Kogoleva; I. V. Zolnikova; P. A. Ilyukhin; E. V. Denisova; S. V. Milash; N. A. Osipova; S. I. Kutsev; A. V. Polyakov; R. A. Zinchenko; et al. (Российский офтальмологический журнал)
Purpose: to evaluate the results of gene therapy by the recombinant adeno-associated viral vector voretigene neparvovec (VN) in children with follow-up periods of 1, 3, 6, and 12 months.Material and methods. The study included 6 children (12 eyes) aged 5 to 15 with a confirmed biallelic mutation in the RPE65 gene, treated with VN (Luxturna, USA). Treatment efficacy was assessed by surveying which included questions on spatial orientation under various types of illumination, Goldman perimetry, microperimetry, best corrected visual acuity (BCVA), electroretinogram (ERG), and visual evoked potentials (VEP). To assess the structure of the retina, the central retinal thickness (CRT) was evaluated by optical coherence tomography.Results. All children showed subjective changes in visual perception, including improved orientation in the dark and twilight, and improved contrast. In one case, the child with initially low visual acuity showed improved visual fixation. In 4 patients out of 6 (8 eyes), an expansion of the visual fields was noted, including 2 cases who displayed significant expansion thereof. In 2 patients (4 eyes), the visual fields were not narrowed and remained so throughout the entire observation period. Mean light sensitivity of the retina in 3 patients and fixation indices in 1 patient improved significantly as shown by microperimetry. BCVA remained stable throughout the study or changed insignificantly. Initially, ERG could not be detected in 8 eyes, but after an VN injection, 6 eyes demonstrated a partial recovery at different times — from 1 to 12 months. An increase in the amplitude of the P1 component to pattern VEP and P2 component to flash VEP was observed in all patients, which indicates an enhanced activity in the projection of the visual cortex after the restoration of the visual cycle. No significant changes were revealed in CRT (p = 0.9). Complications and adverse events were noted in 9 eyes (75 %): chorioretinal dystrophy at the injection site in 3 patients (5 eyes), multifocal nummular dystrophy in 2 patients (4 eyes), local episcleritis in 1 eye, transient increase in intraocular pressure in 2 patients (3 eyes).Conclusion. The results of a one-year post VN treatment follow-up of Russian patients with RPE65-associated inherited retinal disease demonstrate stabilization and improvement of visual functions, which is especially important for otherwise incurable patients with a progressive course of the disease.